2015
DOI: 10.1175/jcli-d-14-00294.1
|View full text |Cite
|
Sign up to set email alerts
|

Regional Simulation of the October and November MJO Events Observed during the CINDY/DYNAMO Field Campaign at Gray Zone Resolution

Abstract: This study investigates the October and November MJO events observed during the Cooperative Indian Ocean Experiment on Intraseasonal Variability in the Year 2011 (CINDY)/Dynamics of the MJO (DYNAMO) field campaign through cloud-permitting numerical simulations. The simulations are compared to multiple observational datasets. The control simulation at 9-km horizontal grid spacing captures the slow eastward progression of both the October and November MJO events in surface precipitation, outgoing longwave radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 104 publications
6
111
0
Order By: Relevance
“…Their definition of NGMS is the ratio between the anomaly of column-integrated vertical advection of MSE to that of DSE. Testing this assumption is complicated by the difficulty of precisely estimating NGMS from observations; however, several modeling and observational studies indicate that NGMS significantly varies with the MJO phase (Benedict et al 2014;SWK;Wang et al 2015;Inoue and Back 2015). SWK found that NGMS increases as the MJO convective active phase passes.…”
Section: Impact Of Assumptions For Simplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their definition of NGMS is the ratio between the anomaly of column-integrated vertical advection of MSE to that of DSE. Testing this assumption is complicated by the difficulty of precisely estimating NGMS from observations; however, several modeling and observational studies indicate that NGMS significantly varies with the MJO phase (Benedict et al 2014;SWK;Wang et al 2015;Inoue and Back 2015). SWK found that NGMS increases as the MJO convective active phase passes.…”
Section: Impact Of Assumptions For Simplificationmentioning
confidence: 99%
“…Because these processes are sources of column-integrated moist static energy (MSE) or moist entropy, it may be useful to focus attention on the budget of that quantity as it varies in association with MJO events. The column-integrated MSE and moist entropy budgets have been studied using numerical simulation outputs (Maloney 2009;Andersen and Kuang 2012;Hannah and Maloney 2014;Benedict et al 2014;Wang et al 2015) and reanalysis datasets (Kiranmayi and Maloney 2011;Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 of Fu et al (2015), although they did not point these explicitly. In contrast, the 76 day simulation of Wang et al (2015) appears to successfully reproduce the strong convection approximately on 6 November. However, the eastern boundary of their regional model was at 120°E and the evolution of the atmosphere in the MC was strongly constrained by the realistic evolution of the atmosphere that is provided to the computational domain as boundary conditions.…”
Section: The Control Casementioning
confidence: 78%
“…Their successful simulation indicates that a proper simulation of a westward moving signal in the western Pacific may be a key to reproduce the enhancement of convection in the MC in early November. Initiation of MJO2 delays by several days in Wang et al (2015). The reason for these earlier or later initiations of MJO2 has not been clarified.…”
Section: The Control Casementioning
confidence: 99%
See 1 more Smart Citation